INCIDENCE OF HEART FAILURE IN DIABETICS WITH CORONARY HEART DISEASE - Stojan Radić (Acta Medica Medianae, 2003)
Heart failure (HF) on the basis of coronary heart disease (CHD) is leading cause of mortality in 37‡62% diabetics. In diabetics CHD is associated with hypertension, central obesity, dislipidemia, hyperfibrinogenemia etc.The aim of this paper was to examine incidence of heart failure in diabetics with CHD, as well as its clinical characteristics compared with nondiabetic patients. We analyzed 478 patients with CHD and exclude patients with, hypertension, dislipidemia, cardiovascular diseases, smokers and other heart failure threatening diseases. We formed two groups with 30 diabetics and 30 nondiabetics.There is no difference in age between genders in diabetics. Nondiabetics males with CHD 45±4.2 year are younger than females 56.2±4.6 (p<0.01). About 33.3% diabetics have heart failure (HF), and 20% nondiabetics, which is statistically important (p=0.1). There is no significant difference in HF incidence between gender in both groups. Nondiabetics females with HF are more obesity than males (27.3±1.5 vs. 26.5±1.4kg/m2), as well as in diabetics (33.6±2.6 vs. 30.7±2.1kg/m2), (p<0.05), which is also seen in patients without HF.Males and females with diabetes mellitus need earlier detection of CHD and earlier therapy in the aim of prevention of HF. The diabetics with myocardial infarct need the permanent control and aggressive therapy on appearing of the first signs of HF.